DESIGNING A LEARNING INFORMATION SYSTEM BASED ON ANDROID (CASE STUDY OF JUNIOR HIGH SCHOOL 4 OF KOTA BUMI) - Handoko, Dwi; Asyhari, Ardian; Al Qusri, Muhammad Fariq (Asia Information System Journal, 2022)
SMP Negeri 4 Kota Bumi in the current learning process only occurs in the classroom during the lesson hours that have been set, where the teacher explains and students take notes, so that if the teacher is unable to attend the student does not get the subject matter, and the same thing happens when the teacher is unable to attend. students do not go to school students will not get the material that takes place that day. The system development method used in this research is the Structured Systems Analysis and Design (SSAD) methodology. This methodology has several important steps that must be carried out in designing and building e-learning at SMPN 4 Kota Bumi. The system to be built is intended to carry out learning activities using information technology so that the expected learning process can be produced using centralized data storage that can facilitate distribution activities. materials, doing practice assignments, and assessments outside of school hours. It is hoped that further development of this academic information system has an Android-based interactive facility that can be installed on the smartphones of all concerned users.